Recent Advances in NAMPT Inhibitors: A Novel Immunotherapic Strategy - Galli, Ubaldina; Colombo, Giorgia; Travelli, Cristina; Tron, Gian Cesare; Genazzani, Armando A.; Grolla, Ambra A. (Frontiers in Pharmacology, 2020)
Nicotinamide adenine dinucleotide (NAD) is a cofactor of many enzymatic reactions as well as being a substrate for a number of NAD-consuming enzymes (e.g., PARPS, sirtuins, etc). NAD can be synthesized de novo starting from tryptophan, nicotinamide, nicotinic acid, or nicotinamide riboside from the diet. On the other hand, the nicotinamide that is liberated by NAD-consuming enzymes can be salvaged to re-form NAD. In this former instance, nicotinamide phosphoribosyltransferase (NAMPT) is the bottleneck enzyme. In the many cells in which the salvage pathway is predominant, NAMPT, therefore, represents an important controller of intracellular NAD concentrations, and as a consequence of energy metabolism. It is, therefore, not surprising that NAMPT is over expressed by tumoral cells, which take advantage from this to sustain growth rate and tumor progression. This has led to the initiation of numerous medicinal chemistry programs to develop NAMPT inhibitors in the context of oncology. More recently, however, it has been shown that NAMPT inhibitors do not solely target the tumor but also have an effect on the immune system. To add complexity, this enzyme can also be secreted by cells, and in the extracellular space it acts as a cytokine mainly through the activation of Toll like Receptor 4 (TLR4), although it has not been clarified yet if this is the only receptor responsible for its actions. While specific small molecules have been developed only against the intracellular form of NAMPT, growing evidences sustain the possibility to target the extracellular form. In this contribution, the most recent evidences on the medicinal chemistry of NAMPT will be reviewed, together with the key elements that sustain the hypothesis of NAMPT targeting and the drawbacks so far encountered.